Adverse Selection and Competitive Market Making: Empirical Evidence from a Limit Order Market - Sandås, Patrik (Review of Financial Studies, 2001)
This article presents a new methodology for testing economic restrictions on the price schedules offered in a limit order book that are based on (i) break-even conditions for marginal limit orders and (ii) rational updating conditions for order book revisions over time. Using order flow data from the Stockholm Stock Exchange, I find strong evidence of insufficient depth in the limit order books relative to the theoretical predictions. An extended model, which allows the model parameters to depend on market conditions, captures some of the systematic variation in the observed order book depth.